Implementasi Model Pembelajaran Kaligrafi Arab (Al-Khaṭtu Al-Naskhi) dalam Meningkatkan Mahārah Al-Kitābah pada Siswa Kelas IX di SMP Pesantren Putri Yatama Mandiri Gowa - Mujahid Abdul Jabbar; Megawati Watngil; Nurfarida Nurfarida; Ansar Ansar (Education and Learning Journal, 2023)
It is known that students' scores for Arabic subjects are still very far below the KKM based on observations in class IX of the Putri Yatama Mandiri Gowa Islamic Boarding School (SKBM). The percentage of complete learning Arabic subjects required is 75. Overall 21 students excel under the SKBM during the pre-cycle. Since only 55% of class students have completed 85% of the required materials, the traditional definition of comprehensive learning has not been met. From the observation data, it is also known that some learning activities are still dominated by teachers, while students choose to do non-learning activities. Al-Khaṭtu Al-Naskhi, a paradigm for learning Arabic calligraphy, was used in a study to address this problem. This research is a classroom action research with two cycles and three meetings per cycle. Planning, executing, observing, and reflecting on tasks are included in each cycle. A total of 26 students of class IX of SMP Pesantren Putri Yatama Mandiri Gowa participated in the learning. Student learning outcomes are determined by pre-cycle evaluation exams, tests given after cycles I and II, and tests given at the end of each traditional learning cycle. The collected data was then examined subjectively and statistically. Learning outcomes data are studied numerically by using descriptive statistics, such as the average value, percentage, and minimum standard of value that must be achieved by students. As can be observed from the findings of hijaiyyah khaṭ naskhi writing skills, there are improvements in four areas as a consequence of the application of the Arabic calligraphy learning model (al-khaṭtu al-naskhi), which creates a pleasant learning environment and improves student learning outcomes. (1) There was an increase in teacher activity by 7.09 between cycles I and II. (2) The level of student activity in cycles I and II also increased by 7.64. (3) The class average increased by 21.15% from cycle I to cycle II, and (4) the presentation of learning completeness increased by 63.39% from cycle I to cycle II. As a result, the Al-Khaṭtu Al-Arab Naskhi Calligraphy Learning Model was successfully implemented.